Promoting the Rural Farm and Nonfarm Businesses : Evidence from the Yemen Rural Investment Climate - Sawada, Naotaka; Zhang, Jian (World Bank, Washington, DC, 2012)
This study examines the major constraints of rural business entry and performance in Yemen. The Yemen rural investment climate survey made it possible to analyze rural investment climate constraints for rural businesses. The survey was used to investigate both farm and nonfarm rural enterprises. The rural investment climate was assessed using a combination of subjective impressions related by rural entrepreneurs, and a more objective, empirical set of analyses that employed indicators to rank the constraints to "doing business" in the areas surveyed. These empirical analyses included application of the entry model, the performance model, the closure model, and the migration model. The migration model was introduced to identify how the rural investment climate variables at the community level increase migration and economic activities. Based on the assessment of the rural investment climate, this paper identifies and explains four critical areas in which the rural investment climate in Yemen can be improved: market demand, access to markets, access to finance, and the provision of business services. Because farm and nonfarm businesses often experience common or similar constraints, the climate in which they operate can often be improved with the same measures and policies. Addressing the constraints that affect rural women entrepreneurs in particular, who play a vital role in rural nonfarm enterprises, warrants clear priority as a means to generate income and employment. Security and labor issues are identified as the key such constraints that disproportionately affect women.